Co-teaching Effectiveness: Students’ Achievement in Mathematical Proficiencies and Content Strands - Muhammad Zafar Iqbal ، Jahan Ara Shams (PJE, 2024)
In Pakistan Mathematics is being taught by single teacher. In contrast coteaching has shown its positive effects on students’ academic achievement in Mathematics. Keeping in view the importance of co-teaching, this study was aimed at examining the co-teaching effectiveness to enhance students’ scores in mathematics. An experimental research design, Solomon Four Group was applied in this study to conduct an experiment. A school in the public sector was selected on convenient basis with due permission of headmaster.